2021
DOI: 10.1021/acschemneuro.1c00306
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Insight into the Mechanisms of Dopamine in Disrupting Aβ Protofibrils and Inhibiting Aβ Aggregation

Abstract: Fibrillary aggregates of amyloid-β (Aβ) are the pathological hallmark of Alzheimer’s disease (AD). Clearing Aβ deposition or inhibiting Aβ aggregation is a promising approach to treat AD. Experimental studies reported that dopamine (DA), an important neurotransmitter, can inhibit Aβ aggregation and disrupt Aβ fibrils in a dose-dependent manner. However, the underlying molecular mechanisms still remain mostly elusive. Herein, we investigated the effect of DA on Aβ42 protofibrils at three different DA-to-Aβ mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 107 publications
1
35
0
Order By: Relevance
“…Considering that the decrease in the ThT fluorescence value from 0 to 6 h with the addition of 50 µM of DA ( Figure 2 A) was steeper than the decrease with the addition of 50 µM of EGCG ( Figure 1 A), the molecular mechanism for Aβ fibril disaggregation may be different between DA and EGCG. Recently, Wei and colleagues reported that both DA and EGCG disrupt the salt bridges between K28 and A42 by molecular dynamics (MD) simulations using the solved Aβ protofibril structure [ 17 , 27 ]. Additionally, MD simulations showed that DA bound to the hydrophobic site containing F4, L34, and V36 disrupts Aβ protofibrils, while EGCG breaks the H-bond between H6 and E11 of Aβ protofibrils [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the decrease in the ThT fluorescence value from 0 to 6 h with the addition of 50 µM of DA ( Figure 2 A) was steeper than the decrease with the addition of 50 µM of EGCG ( Figure 1 A), the molecular mechanism for Aβ fibril disaggregation may be different between DA and EGCG. Recently, Wei and colleagues reported that both DA and EGCG disrupt the salt bridges between K28 and A42 by molecular dynamics (MD) simulations using the solved Aβ protofibril structure [ 17 , 27 ]. Additionally, MD simulations showed that DA bound to the hydrophobic site containing F4, L34, and V36 disrupts Aβ protofibrils, while EGCG breaks the H-bond between H6 and E11 of Aβ protofibrils [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wei and colleagues reported that both DA and EGCG disrupt the salt bridges between K28 and A42 by molecular dynamics (MD) simulations using the solved Aβ protofibril structure [ 17 , 27 ]. Additionally, MD simulations showed that DA bound to the hydrophobic site containing F4, L34, and V36 disrupts Aβ protofibrils, while EGCG breaks the H-bond between H6 and E11 of Aβ protofibrils [ 17 , 27 ]. Similar to our results, the MD simulation studies indicate that the effects of DA and EGCG are different.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, DA can inhibit Aβ aggregation and disrupt Aβ fibrils in a dose-dependent manner ( Huong et al, 2010 ; Liu et al, 2016 ). Recently, Chen et al (2021) reported that DA disrupted Aβ protofibrils and prevented Aβ dimerization at the molecular level mostly through π-π stacking interactions with residues F4, H6, and H13; hydrogen-bonding interactions with negatively charged residues D7, E11, E22, and D23; and cation-π interactions with residue R5. This may be an important mechanism by which DA interferes with Aβ generation.…”
Section: Dopaminergic Systemmentioning
confidence: 99%
“…30,61,63 A salt bridge is considered to be formed when the minimum distance between the NH 3 + group in the main chain of a positively charged Nterminus and the COO À /HPO 3 À group in the side chain of a negatively charged/phosphorylated residue is less than 0.4 nm. [64][65][66][67] Two aromatic rings form p-p stacking interactions when their centroid distance is less than 0.7 nm. 67,68 In all of the statistical analyses, results are the average of the three individual MD trajectories of each system.…”
Section: Discussionmentioning
confidence: 99%